2007 IEEE Particle Accelerator Conference (PAC) 2007
DOI: 10.1109/pac.2007.4441216
|View full text |Cite
|
Sign up to set email alerts
|

New hom coupler design for 3.9 GHZ superconducting cavities at FNAL

Abstract: Over the last few years Fermilab has developed the superconducting third harmonic section for t he FLASH (TTF/DESY) upgrade. Initial v ertical tests of 9 -cell Nb cavities didn't reach the designed accelerating gradient. The main factor of gradient limitation was multipacting in the HOM coupler. In this paper we present the results of vertical tests ac companied with 3D analysis simulations of multipacting. Also we discuss the RF design of the new HOM couplers. The goal of the new design is to eliminate multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 2 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…During the high power test of the No. 2 cavity, thermal breakdown was observed in the HOM coupler with the first barrier occurring at about 1-2 MV=m and the second wider and stronger barrier from 12 to 19 MV=m [27]. Simulation results indicated that the barrier at 1-2 MV=m is MP in zone 1 and the barrier at 12-19 MV=m is MP in zone 3.…”
Section: B Mp In Hom Coupler Of Cavities At Other Frequenciesmentioning
confidence: 92%
See 1 more Smart Citation
“…During the high power test of the No. 2 cavity, thermal breakdown was observed in the HOM coupler with the first barrier occurring at about 1-2 MV=m and the second wider and stronger barrier from 12 to 19 MV=m [27]. Simulation results indicated that the barrier at 1-2 MV=m is MP in zone 1 and the barrier at 12-19 MV=m is MP in zone 3.…”
Section: B Mp In Hom Coupler Of Cavities At Other Frequenciesmentioning
confidence: 92%
“…The highest barrier we predict is above the experimentally achieved gradient. It should be mentioned that the original HOM coupler in the third harmonic cavity was ultimately redesigned and MP was successfully avoided [27].…”
Section: B Mp In Hom Coupler Of Cavities At Other Frequenciesmentioning
confidence: 99%
“…It is also equipped with two HOM couplers installed on either side of the connecting beam pipes with different rotations as shown in Fig. 1 [23]. The HOM couplers with one post (Fig.…”
Section: Third Harmonic Cavitiesmentioning
confidence: 99%
“…We can also obtain the loaded quality factor with the measurements of the power decay time constant from the cavity transmitted power curves in the field probe port at cryogenic temperature and high-power conditions, as shown in Figure 8.16. Improved design of the heat sinks [25], [32] of HOM coupler to the cryogenic system has provided sufficient cooling to run the SC cavity at high gradient and 5 Hz repetition rate.…”
Section: Cavity Performance Testmentioning
confidence: 99%